Effects of the upwelling system on the assessment of reproductive parameters of the caridean shrimp Nematopalaemon schmitti (Holthuis, 1950) in the Western Atlantic - Herrera, Daphine R. [UNESP]; Davanso, Thiago Maia; Costa, Rogerio C. [UNESP] (Wiley, 2021)
Costal upwelling and other oceanographic features exert important effects on neritic and benthic communities, causing variations in the reproduction and survival of organisms. Here, we assessed the population structure, sex ratio, recruitment, and reproduction of the caridean shrimp Nematopalaemon schmitti near the Cabo Frio upwelling area in southeastern Brazil. In total, 759 individuals were captured. N. schmitti exhibited a unimodal size–frequency distribution pattern with larger females, and the binomial test indicated a significantly female-biased sex ratio. The time-series analysis showed synchrony between ovigerous females and juveniles that revealed continuous reproduction and the possible existence of recruitment areas. Our findings indicate that reproductive parameters are influenced by the environmental factors of the region studied here. We advocate that the influence of the sedimentary composition of the soft bottom and upwelling system of Cabo Frio is the predominant factors influencing the reproductive parameters in N. schmitti.
Keywords: crustacean; environmental factors; population structure; recruitment; reproductive strategy; sex ratio